1997
DOI: 10.1183/09031936.97.10020388
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary endocrine cells in anthracosilicotic lungs

Abstract: It has been suggested by some studies of human and animal lungs that the products of pulmonary endocrine cells, particularly gastrin-releasing peptide, might play a role in fibrogenesis, but more recent detailed studies of fibrotic human lungs have failed to confirm this. We have made a detailed quantitative examination of a series of fibrotic human lungs to see if we could determine whether there was any relationship between endocrine cells and fibrosis.Using immunocytochemistry, we investigated the morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The increase in neuroendocrine cells was also confined to areas of lung affected by acute bronchitis and bronchopneumonia, leading the authors to speculate that inflammation rather than fibrosis is a causative factor of NECH. 24 Aguayo et al reported a ten-fold increase in neuroendocrine cells in eosinophilic granuloma by bombesin-like peptide immunoreactivity compared to smokers and patients with idiopathic pulmonary fibrosis. Normal lung tissue was not examined in the study, however, the frequency of approximately 6-8 cells per 10 cm of airway epithelial length is comparable to the frequency of neuroendocrine cells in normal autopsy lungs as reported by Gosney et al 13,25 A single case report has described NECH as a rare cause of interstitial lung disease in two patients, both of whom were female non-smokers living above sea level.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in neuroendocrine cells was also confined to areas of lung affected by acute bronchitis and bronchopneumonia, leading the authors to speculate that inflammation rather than fibrosis is a causative factor of NECH. 24 Aguayo et al reported a ten-fold increase in neuroendocrine cells in eosinophilic granuloma by bombesin-like peptide immunoreactivity compared to smokers and patients with idiopathic pulmonary fibrosis. Normal lung tissue was not examined in the study, however, the frequency of approximately 6-8 cells per 10 cm of airway epithelial length is comparable to the frequency of neuroendocrine cells in normal autopsy lungs as reported by Gosney et al 13,25 A single case report has described NECH as a rare cause of interstitial lung disease in two patients, both of whom were female non-smokers living above sea level.…”
Section: Discussionmentioning
confidence: 99%